[Rezension von: Alstola, Tero, 1987-, Judeans in Babylonia : a study of deportees in the sixth and fifth centuries BCE] - Spunaugle, Adrianne (Journal of the American Oriental Society, 2023)
Judeans in Babylonia: A Study of Deportees in the Sixth and Fifth Centuries BCE. By Tero Alstola. Culture and History of the Ancient Near East, vol. 109. Leiden: Brill, 2020. Pp. xii + 353. $150.